EXPLORING EXTENSIVE READING FROM STUDENTS’ PERSPECTIVE - Diska Fatima Virgiyanti; Hesti Rokhaniyah; Aries Fachriza (Jurnal Review Pendidikan dan Pengajaran (JRPP), 2023)
Extensive reading becomes familiar among students since this activity eases them to read anytime and anywhere they like. Besides, they were also given the freedom to read any kind of book genre. The goal of this activity is to assist students in improving their reading skills. This research design is a descriptive qualitative where the respondents are twelve students of English Language Education Department. This research aims to investigate the students’ perspective toward extensive reading. The data collection was done by interviewing the respondents, doing field observation, and analyzing documents to confirm the data to support the triangulation. The results of the study showed that extensive reading was able to improve students' reading comprehension, increased students’ interest in reading, and built students’ awareness of the importance of literacy and having good reading habits. Furthermore, it should be highlighted that the students and lecturers have the capability and chance to produce readable sources to promote extensive reading at the level of elementary, junior, and senior high school or even at the university level.